Political theory and Republicanism Imaginary and historicity - A necessary debate - Castillo Ochoa, Manuel (2019)
Soon, in the year 2021, Peru will reach its bicentennial as a Nation. That is why a debate has arisen and crosses not only the domains of national historiography but even those of the social sciences as a whole. That «revival» of the republican state proposal, it is not new in Peru, but may be so, now that it is confronted and on the other hand, in relation to the consequences that these actions will involve to give way interpretations of the configuration of the Peruvian reality. The present article inquiries about that theoretical, political and republican rebirth, analysing the scope of one of its main disseminators. Thus, it seeks to present a theoretical balance, of the same, from the tradition of national critical thinking.